Perceived Causes and Attitudes Regarding Overindebtedness and Their Effects on Public Agreement With Government Financial Aid - Soro, Jerônimo C.; Ferreira, Mário B.; de Almeida, Filipa; Silva, Carla Sofia; Reis, Joana (Frontiers in Psychology, 2021)
In order to better understand how the problem of overindebtedness is perceived from a laypeople standpoint, Study 1 inquired both overindebted and non-overindebted consumers on the perceived causes of and attitudes towards the overindebted. Situational and dispositional factors were perceived to have similar impact as causes of overindebtedness, but non-overindebted consumers showed stronger agreement with those causes than overindebted consumers. Regarding attitudes, non-overindebted consumers tended to blame overindebted people for their situation rather than perceiving them as victims, whereas overindebted consumers showed the opposite pattern. Study 2 used a sample of (non-overindebted) consumers to assess the impact of perceived causes of overindebtedness, attitudes towards the overindebted, and political orientation on public support of government policies for aiding overindebted people. We discuss the contributions of the present findings to design public policies aimed at aiding overindebted households that are more aligned with the beliefs and attitudes of the general public.